A comparison of the European Union's accession negotiations with Bulgaria and Turkey: the role of bilateral issues. Issue 2 (3rd April 2017) - Müftüler-Baç, Meltem; Cicek, Aylin Ece
Abstract: This paper compares the EU's accession negotiations with Bulgaria and Turkey to assess the conditions under which their negotiations unfolded and the role of bilateral issues in that aspect. To do so, the paper highlights the role of the member state vetoes and bilateral relations in the EU negotiations. It needs to be noted that even though the European Commission condemns the impact of bilateral problems on the accession process, unresolved bilateral issues, nonetheless, emerge as major factors complicating the EU's enlargement process, its effectiveness as well as the pace and nature of the negotiations with multiple applicants and candidates. We look at role of individual member states as veto players on the EU accession negotiations, specifically becoming the most important factor in the Turkish case. We limit our focus to the lack of consensus and commitment among the EU member states towards Turkey as a complicating factor in the EU negotiations. We are able to ascertain that a key difference between Bulgaria and Turkey with regards to their EU accession was the member state vetoes for Turkey's negotiations.